Pengembangan Bahan Ajar Menggunakan Aplikasi Kvisoft Flipbook Maker Materi Himpunan - Wibowo, Edi; Pratiwi, Dona Dinda (Desimal: Jurnal Matematika, 2018)
This study aims to develop e-module teaching materials by applying kvisoft flipbook maker on the subject of the set. To view teacher and learner responses to e-module teaching materials using the kvisoft flipbook maker application on the subject of the set. The method of this research was conducted using Research & Development method of Borg and Gall model which has been modified by Sugiyono covering 7 stages: 1) Potential and Problem, 2) Collecting Data, 3) Product Design, 4) Design Validation, 5) Design Revision, 6) Product Trial, 7) Product Revision. The results of this study indicate that the value of feasibility by the material experts scored an average of 3.23 with good criteria and value of feasibility by media experts with an average score of 3.28 with very good criteria, while the value of feasibility by linguists got a flat score 3.02 with good criteria. The response of the students was very interesting, with the achievement of the average score of 3.33 small group trials and the achievement of the average score of 3.49 field trials, the teacher's test response was very interesting with the achievement of an average score of 3.64. This shows that the e-module using the kvisoft flipbook maker application generated in this study is considered feasible for use in the mathematics learning of the set matter.